Drafting method of atmospheric air condition monitoring - Mukasheva, M.A.; Ruppel , A. (Fundamental and Experimental Biology, 2016)
Currently, in the existing methodological recommendations covered issues of ranging areas based on quantitative and qualitative analysis criteria, using air-route and under torch samples. In modern conditions for the control of air pollution are necessary techniques to provide an adequate assessment of the degree of air pollution with minimal physical, technical and financial costs. Evaluation of air pollution with the help of maximum permissible concentration is carried out with the mandatory condition of coincidence of their temporal characteristics with the timing of the actual pollutant concentrations in the atmospheric air. For assessing the degree of air pollution.